Melatonin Rescued Reactive Oxygen Species-Impaired Osteogenesis of Human Bone Marrow Mesenchymal Stem Cells in the Presence of Tumor Necrosis Factor-Alpha - Xianjian Qiu; Xudong Wang; Jincheng Qiu; Yuanxin Zhu; Tongzhou Liang; Bo Gao; Zizhao Wu; Chengjie Lian; Yan Peng; Anjing Liang; Peiqiang Su; Dongsheng Huang (Stem Cells International)
Accumulation of reactive oxygen species (ROS), which can be induced by inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), can significantly inhibit the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). This process can contribute to the imbalance of bone remodeling, which ultimately leads to osteoporosis. Therefore, reducing the ROS generation during osteogenesis of BMSCs may be an effective way to reverse the impairment of osteogenesis. Melatonin (MLT) has been reported to act as an antioxidant during cell proliferation and differentiation, but its antioxidant effect and mechanism of action during osteogenesis of MSCs in the inflammatory microenvironment, especially in the presence of TNF-α, remain unknown and need further study. In our study, we demonstrate that melatonin can counteract the generation of ROS and the inhibitory osteogenesis of BMSCs induced by TNF-α, by upregulating the expression of antioxidases and downregulating the expression of oxidases. Meanwhile, MLT can inhibit the phosphorylation of p65 protein and block the degradation of IκBα protein, thus decreasing the activity of the NF-κB pathway. This study confirmed that melatonin can inhibit the generation of ROS during osteogenic differentiation of BMSCs and reverse the inhibition of osteogenic differentiation of BMSCs in vitro, suggesting that melatonin can antagonize TNF-α-induced ROS generation and promote the great effect of osteogenic differentiation of BMSCs. Accordingly, these findings provide more evidence that melatonin can be used as a candidate drug for the treatment of osteoporosis.